(untitled) (Nexo Revista Científica, 2021)
The purpose of this study is to contextualize the digital literacy of university students within the current pandemic, taking into account the development of skills and challenges of this new digital era. Analyze, in addition, its scope and limits for the development of students, who continue with their professional studies despite confinement. It was a quantitative-descriptive study, with sociodemographic variables (age, sex, time of connectivity); The sample consisted of engineering students from a public university: 213 men (64.5%) and 117 women (35.5%) from the fifth cycle of the degree. The Area instrument (2014) was used. Digital literacy and the formation of citizenship of the XXI century. We conclude that digital literacy will continue to expand more and more, since education is based on virtuality due to the covid-19 pandemic, so that this modality will continue to expand so that students continue with their higher studies normally, developing technological knowledge.